Summative evaluation of community extension project: A phenomenological inquiry - HELEN Q. OMBLERO (Journal of Advanced Research in Social Sciences and Humanities, 2020)
Aim: The research was conducted to see if the project should be scrapped, and the results were used to make that decision. Bansayalangsa Kalambuansa Katawhan is a community outreach initiative started by the Social Work Program. Participants received instruction in environmental sanitation and leadership, organizational, and project management.Method: Twenty-one (21) people participated in the Focus Group Discussion (FGD) and individual interviews. Positive responses were received from those who benefited from the research findings in the areas of increased income, empowered leadership, heightened environmental awareness, and enhanced skills.Findings: This finding demonstrates the value of the academic community’s ability to provide extension services to local communities, which benefits the nation as a whole.Implications/Novel Contribution: Community social workers will benefit from the findings of this study. To be the paragon of solid leadership, trust, and integrity, they must display passion, patience, knowledge, and wisdom.